Design of an experiment for the biomechanical and thermal analysis of athletes during prolonged running exercise - Crenna, F.; Tanda, G. (Journal of Human Sport & Exercise, 2022)
Biomechanics and thermoregulation of human running are key aspects playing an important role in the training of professional athletes. In the case of a prolonged exercise, as occurs during the marathon race, the intensity and duration of the exercise (in concert with environmental conditions) can affect the thermoregulatory response and the running mechanics. The aim of this study is the design of a novel experiment able to simultaneously capture information concerning the biomechanics of lower limbs and the surface temperature map of the whole body during a prolonged running exercise on treadmill. Kinematics quantities, such as linear and angular displacement, velocity and acceleration of relevant body markers are recorded by a video system, while surface temperature evolution on time is detected by an infrared thermal camera. A group of five amateur athletes, with long experience in long-distance running competitions, was involved in this study. Results for the sample group, in terms of kinematic (displacements and angles) and thermal (local and total-body skin temperatures) quantities, revealed features related to individual response to the effort. Even though the relatively little number of athletes does not permit to infer general conclusions, the combined mechanical and thermal experiment is deemed to be a useful tool for the investigation of endurance running characteristics.